PENGARUH RASIO KEUANGAN DAERAH, DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP ALOKASI BELANJA MODAL (Studi Empiris pada Kabupaten/Kota Provinsi Riau Tahun 2013-2017) - Zetty Iqmi; Nasrizal Nasrizal; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research was examined the influence of Local Government Financial Ratio,General Allocation Funds And Regency Own Revenue to Capital Expenditure AtKabupaten/Kota On Riau Province At Years 2013-2017. The population in this study areall Kabupaten/Kota at Riau Province. This research is included in quantitative research.The type of data used in this study is secondary data from Laporan Rencana Anggaran(LRA) of the aforementioned Kabupaten/Kota on Riau Province and data derived fromthe Dirjen Perimbangan Keuangan Pemerintah Daerah website www.djpk.depkeu.go.id,sampling is done by the method of purposive sampling is the technique of sampling withcertain considerations. The total sample in this study are 11 Kabupaten/Kota. These datawere analyzed using multiple regression analysis with SPSS Version 17. The results ofthis study showed that Local Government Financial Ratio affects Capital Expenditurewith significant value 0,006, so the conclusion Hypothesis 1 accepted, General AllocationFunds affects Capital Expenditure with significant value 0,015, so the conclusionHypothesis 2 accepted and Regency Own Revenue affects Capital Expenditure withsignificant value 0,000, so the conclusion Hypothesis 3 accepted.Keywords : Capital Expenditure, Local Government Financial Ratio, GeneralAllocation Funds, Regency Own Revenue